Response fermented goat urine by EM4 on Productivity of Legum Stylosanthes guianensis and Arachis pintoi - Fajar Bahari Ginting; nevy diana hanafi; hasnudi hasnudi (Jurnal Agroekoteknologi, 2019)
Utilization of EM4 fermented goat urine as organic fertilizer that can improve productivity of legumes Stylosanthes guianensis and Arachis pintoi. The study was conducted in field laboratory Animal Science Study Program Faculty of Agriculture, University of Sumatera Utara in June to November 2017, using a randomized block design factorial divided into 2 factor, composed of  the type of legume (Stylosanthes guianensis and Arachis pintoi) and the fertilizer dose (0, 100, 150, 200, 250 ml / polybag). The variables observed were plant height, fresh weight production and dry matter production. The results showed that increasing dose  fermented goat urine give the very real result (P<0.01) increased plant height, fresh weight production and dry matter production and the productivity Stylosanthes guianensis hed nigher Arachis pintoi plant height, fresh weight production and dry matter production it is concluded that increased dose fermented goat urine increased on productivity of  Stylosanthes guianensis and Arachis pintoi. Keywords: fermented goat urine, Stylosanthes guianensis, Arachis pintoi, productivity, fertilizing dose.